Evaluación cefalométrica del acompañamiento de los tejidos duros a los tejidos blandos en cirugía bimaxilar con seguimiento de ocho meses (2007)
ABSTRACT: The purpose of this longitudinal descriptive study was to evaluate the behavior of soft tissues in patients who underwent bimaxilar ortognatic surgery at the Hospital University San Vicente de Paul (HUSVP) by means of lateral cephalic headplates. A total of twenty one patients selected by convenience, with an average age of 22,8 years, were treated , all of them received lateral cephalic headplates pre and post surgery. All of the subjects had received pre-surgical orthodontic treatment, they also received LeFort I surgery of impactation and maxilar advance, the mandible was retruded using a sagittal technique of the ramus. A different behaviour to the one found in different ethnic groups was found in this population. The movement in the horizontal plane showed an ascending path from the nasal point up to the upper superior point of the lip. For the nasal point a 46.9% movement was found. For the sub nasal and the superior anterior point of the lip a movement of 63.5% and 73% respectively. For the mandible the movement was51.0 % for labralis superius, point point B followed with 82.9 % and pogonion with 75%. In the vertical direction the movement was 67% for the nasal point, 64% for sub nasal point and 50% for the labralis superior. The mandible showed a movement of 34, 7% for labralis inferior and an average of 67,7% for the remaining points of the mandible. In conclusion, it is important to consider the ethnic characteristics of our population and the type of surgery, since they presented a different behavior than the one reported in the literature.